DIELECTRIC PROPERTIES OF THE NATURAL, MODIFIED AND IRRADIATED ZEOLITES (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
Dielectric permittivity  (ε=ε՛–iε՛՛)  of the natural, modified and irradiated zeolite is measured depending on frequency of a variable electrical field. It has been carried out that dielectric permittivity and dielectric losses factor of Ba2+ modified zeolite depending on electric field frequency monotonously decreases. With increase of a doze of an irradiation up to 1015 el/cm2 the maximum of dielectric parameter is observed, and at a doze of 3‧1016 el/cm2 this parameter strongly decreases. It is supposed, that such behaviour of tanδ is connected with occurring structural changes in the elementary cell of zeolite at introduction of ions Ba2+ and irradiation.
Keywords: zeolite; dielectric losses; modified and irradiated zeolite